Radiogenic heat production drives Cambrian–Ordovician metamorphism of the Curnamona Province, south-central Australia: Insights from petrochronology and thermal modelling - De Vries Van Leeuwen, A.T.; Raimondo, T.; Morrissey, L.J.; Hand, M.; Hasterok, D.; Clark, Chris; Anczkiewicz, R. (2023)
Multi-mineral petrochronology can effectively track changes in the thermochemical environment experienced by rocks during metamorphism. We demonstrate this concept using garnet–chlorite schists from the Walter-Outalpa Shear Zone of the southern Curnamona Province, South Australia, which reveal a cryptic and protracted (c. 39 Myr) record of high thermal gradient metamorphism. Petrochronological data including in situ monazite U–Pb and garnet Lu–Hf and Sm–Nd dating suggest elevated geotherms were persistent between at least c. 519–480 Ma, throughout the duration of garnet growth. Additional in situ xenotime U–Pb dating implies that partial garnet breakdown occurred between c. 480–440 Ma, likely induced by fluid-rock interaction or exhumation. Although metamorphism temporally overlaps with the timing of the regional Delamerian Orogeny (c. 520–480 Ma), the thermal mechanism to sustain elevated temperatures has remained enigmatic. One-dimensional thermal models are used to appraise the role of radiogenic heat production in driving the observed high thermal gradient metamorphism. The models reveal that with only modest crustal thickening during orogenesis, the endogenous radiogenic heat production hosted within the basement rocks could plausibly provide the thermal impetus for metamorphism.